Behind the Great Recession: Job Search and Housing Decisions - Silvio Rendon; Núria Quella (Institute for the Study of Labor (IZA), 2013)
In this paper we analyze a mechanism that is particularly relevant to the workings of the Great Recession: we explain how easier home financing and higher homeownership rates increase unemployment rates. To this purpose we build a model of job search with liquid wealth accumulation and consumption of housing that can be rented, bought on credit, or sold. In our model, more relaxed house credit conditions increase workers' reservation wages, making them more selective in their job search. More selective job searches deteriorate employment transitions: job finding and job-to-job transitions rates decline while job loss rates increase, causing the overall unemployment rate to rise. We estimate this model structurally using NLSY data from 1978 until 2005. We find that more relaxed housing lending conditions, particularly lower downpayment requirements, increase unemployment rates by 6 percent points. We also find that declining labor demand decreases homeownership rates by 14 percent points.
Keywords: J64; E21; E24; R21; 330; job search; housing; savings; structural estimation